Online English Learning and Adult Employability in Brazil: A Thematic Literature Review - Umezaki, Janna Ria; Basco-Igot, Janette; Dorado, Mc Chem (JPAIR Institutional Research, 2026)
This thematic literature review examines the relationship between online English learning and adult employability in Brazil within the context of digital transformation and labor-market restructuring. Drawing on peer-reviewed studies and institutional reports published between 2020-2025, the review synthesizes findings across four interrelated themes: flexibility and accessibility of online English learning; language development, learner autonomy, and engagement; links between English proficiency and employability outcomes; and structural barriers related to digital inequality and program quality. The reviewed literature suggests that online English learning can enhance adults' communicative competence, confidence, and perceived employability, particularly in sectors associated with internationalization, technology, and remote work. However, benefits are unevenly distributed, as access to digital infrastructure, prior educational background, and socioeconomic conditions significantly mediate outcomes. Moreover, the predominance of self-reported employability measures limits causal inference. This review contributes a Brazil-focused thematic synthesis that situates online English learning within broader debates on employability, adult education, and digital inequality, and identifies priorities for policy development and future research aimed at promoting more equitable workforce participation.
Keywords: online English learning; adult employability; e-learning; adult education; Brazil